THE EFFECT OF DIFFERENT FUEL TYPES ON THE OPERATION OF AUTOMOBILE ENGINE CYLINDERS (Journal of Multidisciplinary Sciences and Innovations, 2025)
Car engines cylinders is the " heart " of the car , their performance and used fuel​ type directly Depends. Fuel type of the engine efficiency, power, waste gases and to the endurance impact does. In Uzbekistan car industry, in particular UzAutoMotors, gasoline and diesel to fuels based although  naturally gas, biofuel and hydrogen such as alternative fuels increasingly attention is gaining. This article various fuel​ types car engine cylinders to work the impact analysis does.